Analysis Of Village Government Performance In Natural Resource Management In The Coastal Area Of East Olilit Village, South Tanimbar District, Tanimbar Islands Regency - Melsasail, Theresia T.S.; Pieter Sammy Soselisa; Hengky V.R. Pattimukay (Journal of International Multidisciplinary Research, 2024)
This research was conducted in October 2023 with the aim of analyzing the performance of the village government in managing natural resources in the coastal area of East Olilit Village, South Tanimbar District, Tanimbar Islands Regency. The results of this study were obtained using a qualitative descriptive method, in which the author assessed the performance indicators of the village government in managing natural resources in the coastal area through observation techniques, interview techniques, and documentation techniques. Based on the results of this study, it can be concluded that the performance of the village government in managing natural resources in the coastal area of East Olilit Village is quite good, and the East Olilit Village government has undertaken replanting of trees around the coastal area affected by abrasion.